Ideas preliminares sobre la construcción de un sistema para la divulgación de información a través del teléfono celular sin intermediación de operadores telefónicos (2019)
The permanent evolution of the TIC offers more and better tools to facilitate the pertinentaccess to the organizational information (data, audio, and video) every day.The information is nowadays the fundamental asset of any organization, therefore it becomesessential to find efficient mechanisms for administering and presenting it; the academicsurroundings are not the exception, the universities daily generate hundreds of kilobytes ofinformation that must be received complete and on time by the different members of theircommunities.This article presents the foundations of a proposal oriented to the implementation of a Systemfor the Spreading of Information through the mobile phone that allows the organizations totake advantage of the covering, massive use and easy way to acquire this technology in order to offer a service without the intermediation on the part of the operators of the telephoneservice (therefore without cost).